O teorema central do limite: um estudo ecológico do saber e do didático - Rodrigues, Chang Kuo (2009)
This paper refers to the building of mathematical and/or statistical ideas and concepts around Central Limit Theorem for Mathematics graduates.The investigation focuses the importance of the theorem in Statistics Inference and its comprehension by the professionals to be, who will act in Basic Education. Therefore, we chose to research some books related to the teaching and learning process of the theorem and emphasised its importance on the Mathematics teacher daily practice. The theoretical approach is about Mathematics Teaching theories, particularly the Theory of Didactic Transposition ( CHEVALLARD, 1985), with an echological approach under the knowlwdge and teaching point of view ( ARTAUD, 1998). We chose methodological procedures directed to the didactic design (ARTIGUE, 2009), with qualitative nature, and whose assumptions are linked to Teaching Engineering (ARTIGUE, 1988). The subjects of this investigation are the graduates who had some knowledge about Basic Statistics and, from a previous analysis about the kind of knowledge they had about the theme, we presented some activities in a problem-situation context connected to the Mathematics teachers daily practice. The analysis of these results allowed us to relate the existing problems between the subject and the students from Basic Education, which involved statistics literacy. After these activities, there was a dialogue, with discussions about the theme, allowing us to analyse how the ideas and concepts around the Central Limit Theorem were built, being its comprehension the main aim for the graduates. Besides that, we analysed some textbooks for higher education, based on the Anthropological Theory of Didactic (CHEVALLARD, 1996, 1999), which also showed us the essential knowledge for the theorem to live , because the approach is under the knowledge and teaching echological point of view. On the other hand, we detected what kind of limitations, or restrictions, exist in the books analysed, interfering in the elaboration of the activities by the teacher. Thus, our investigation reaffirms the importance of teaching and learning Statistics in the various applications for the Mathematics teachers to be formation in a world controlled by the technological advances, which interfere directly on the understanding of the information we receive every moment